Laboratory Assessment of the Anticoagulant Activity of Apixaban in Patients With Nonvalvular Atrial Fibrillation. (December 2018) - Kyriakou, Elias; Katogiannis, Konstantinos; Ikonomidis, Ignatios; Giallouros, George; Nikolopoulos, Georgios K.; Rapti, Evdoxia; Taichert, Maria; Pantavou, Katerina; Gialeraki, Argiri; Kousathana, Foteini; Poulis, Aristarchos; Tsantes, Andreas G.; et al.
Our aim is to determine the most appropriate laboratory tests, besides anti-factor Xa (anti-FXa) chromogenic assays, to estimate the degree of anticoagulation with apixaban and compare it with that of rivaroxaban in real-world patients. Twenty patients with nonvalvular atrial fibrillation treated with apixaban 5 mg twice daily and 20 patients on rivaroxaban 20 mg once daily were studied. Conventional coagulation tests, thrombin generation assay (TGA), and thromboelastometry (nonactivated TEM [NATEM] assay) were performed in the 40 patients and 20 controls. The anti-FXa chromogenic assays were used to measure apixaban and rivaroxaban plasma levels. The NATEM measurements showed no significant difference between the 2 groups of patients. Concerning TGA, endogenous thrombin potential (ETP) was significantly decreased in patients on rivaroxaban as compared to those treated with apixaban ( P < .003). A statistically significant, strong inverse correlation between apixaban plasma concentrations and ETP ( P < .001) was observed. Apixaban significantly reduces ETP compared to controls, but to a lesser extent than rivaroxaban. Thrombin generation assay might provide additional information on apixaban exposure, which is required in order to individualize treatment especially for patients with a high bleeding risk. Our findings have to be further investigated in studies with larger sample sizes, in the entire range of apixaban exposure, with other direct oral anticoagulants, and in relation to clinical outcomes.